Incidence of type 1 diabetes in 0 to 14 year olds in Australia from 2002 to 2017. Issue 5 (31st May 2020) - Haynes, Aveni; Bulsara, Max K.; Bergman, Phil; Cameron, Fergus; Couper, Jennifer; Craig, Maria E.; Demangone, Karen; Johnson, Stephanie; Lafferty, Antony; Titmuss, Angela; Davis, Elizabeth A.
Abstract: Objective: To determine the incidence of childhood onset type 1 diabetes in Australia from 2002 to 2017, and analyze incidence rate trends by calendar year, sex, and age at diagnosis. Research Design and Methods: Children newly diagnosed with type 1 diabetes aged <15  years between 2002 and 2017 were identified from the National Diabetes Register, estimated to be ~99% complete. Data were obtained for diagnosis year, sex, age, and residential State/Territory at time of diagnosis. Population estimates by year, sex, single year of age, and State/Territory were obtained from the Australian Bureau of Statistics and Poisson regression used to examine incidence and trends by calendar year, sex, and age group at diagnosis. Results: Between 2002 and 2017, there were 16 783 newly diagnosed cases of type 1 diabetes in children aged < 15 years (8684 boys: 8099 girls), giving a mean incidence of 25.0/1 00 000 person years (95%CI: 24.6, 25.4). A sinusoidal pattern in the incidence rate trend was observed with 5‐yearly cycles providing the best model fit. No significant difference was observed in boys compared to girls (IRR 0.98 [95%CI: 0.95, 1.01]). Compared to 0 to 4  year olds, the mean incidence was 75% higher in 5 to 9  year olds, and 224% higher in 10 to 14 year olds. A decreasing incidence rate trend was observed in 0 to 4  year old boys and girls. Conclusions: This study reports updated incidence and incidence rate trends in children and adolescents diagnosed with type 1 diabetes in Australia. A cyclical pattern in incidence trend persists, with an overall decreasing trend observed only in the youngest age group.